MORPHOLOGICAL CHARACTERISTICS OF MUCOSAL VASCULARIZATION IN THE SEPTUM AND INFERIOR WALL OF THE FRONTAL SINUS IN PHYSIOLOGICAL NORM - Serbin, S.I.; Dubyna, S.O.; Bondarenko, S.V.; Tykhonova, O.O.; Tarasenko, Ya.A.; Koptev, M.M.; Danylchenko, S.I. (Актуальні проблеми сучасної медицини: Вісник Української медичної стоматологічної академії, 2025)
Relevance. The frontal sinus plays a significant role within the paranasal sinus system, as the progression of pathological processes, particularly inflammatory conditions, often presents with clinical features distinct from those of other paranasal sinuses. Diseases affecting the paranasal sinuses remain among the most pressing challenges in contemporary otorhinolaryngology. Objective. The purpose of this study was to obtain data on the angioarchitectonics of the mucosa in the septum and the inferior wall of the frontal sinus in clinically healthy individuals. Materials and method. For the study, cadaver material of persons of both sexes aged from 24 to 76 years was used (38 cadavers: 24 men / 14 women), those who died from causes unrelated to the pathology of the paranasal sinuses were examined in accordance with international standards of biological research and guidelines. Histotopographic, histological, histochemical and morphometric data with statistical analysis of the results were used to expand the understanding of the microscopic structure of the frontal sinus mucosa. Statistical analysis of the morphometry data confirmed and supplemented the differences in the vascularization of the mucous membrane of the lower wall with the human frontal sinus septum. The histological study gave an idea of the structural organization of the human frontal sinus mucosa in the context of angioarchitectonics. Results. The angioarchitectonics of the frontal sinus mucosa is represented by vessels of two groups: the first includes arteries and veins, which represent a deep network, the second includes arterioles, capillaries and venules, components of the superficial vascular network. It was established that the wall of both groups of vessels on both walls had signs of a classical structure. The most prominent vessels among all examined were the arterioles of the inferior wall in the frontal sinus, which had 4-6 layers of smooth myocytes in the middle sheath of their walls, compared to the arterioles of the septum, which had 1-2 layers. In the morphometric part of the study, it was shown that the diameter of all the investigated vessels on the specified walls did not have a significant difference, the only exception were veins with a difference within 5%. Conclusion. The data obtained allow us to suggest about possible complications due to inflammatory processes in the frontal sinus, as well as the patterns of their spread to the surrounding structures of the skull, including the orbit and other paranasal sinuses.